(untitled) (Journal of Information and Communication Technology, 2019)
Many children have limitations that significantly impact their writing ability, such as physical, cognitive, and motor limitations, all of which need to be overcome for a good level of written expression. This study addresses problems and difficulties in mastering the process of writing among dysgraphic children. The most suitable method to overcome these problems is to provide activities and exercises that can help students improve visual-motor integration that is correlated with writing skills. With this aim in mind, a dysgraphic-customised application called Write-Rite has been designed to support children, through activities and exercises, in order to fulfil their unique needs. This study attempted to design and evaluate Write-Rite application that provides a stimulating and interactive experience for dysgraphic children to practise writing at different levels of difficulties, which could facilitate the learning process. This research was conducted in two primary school in Kedah, where five participants (age seven to twelve) were studied and evaluate for five weeks. Data was compiled by using an observation, recorded handwriting performance and a self-generated rubric to track the following: letter formation, slant, size and proportion, alignment, spacing and line quality. The results of a preliminary evaluation and assessment of â€œWrite-Riteâ€ concluded that this application has justified its role in terms of optimisation in writing proficiency among dysgraphic children.